PENGARUH LABA BERSIH, ARUS KAS OPERASI DAN KOMPONEN-KOMPONEN AKRUAL DALAM MEMPREDIKSI ARUS KAS OPERASI DI MASA DEPAN - Wahyu Sulistyawan; Aditya Septiani (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to examine about the influence of earning, operation of cash flows, and accrual components in predicting cash flow operations in the future of the manufacturing companies. This research using four accrual components as independent variable, namely changes in receivables, changes in payables, changes in inventories, and changes in depreciation. The type of data that is used in this research was secondary data from the financial statement manufacturing company registered in indonesia stock exchange in 2009-2013. Thesample collection in this research is done by purposively sampling to manufacturing companies in indonesia. This research using model of multiple regression. The results shows that earning, operation of cash flow, changes in receivables changes in payables, changes in inventories and changes in depreciation costs significantly affect to the future operation cash flow